1.7k views
0 votes
The same exponential growth function can be written in the forms y() - yo e t, y(t)- yo(1 r, and y) yo2 2. Write k as a function of r, r as a function of T2, and T2 as a function of k Write k as a function of r. k(r)-

1 Answer

0 votes

Answer:


(a)\ k(r) = \ln(1+r)


(b)\ r(T_2) = 2^(1/T_2)-1


(c)\ T_2(k) = (\ln(2))/(k)

Explanation:

Given


y(t) = y_0e^(kt)


y(t) = y_0(1+r)^t


y(t) = y_02^(t/T_2)

Solving (a): k(r)

Equate
y(t) = y_0e^(kt) and
y(t) = y_0(1+r)^t


y_0e^(kt) = y_0(1+r)^t

Cancel out common terms


e^(kt) = (1+r)^t

Take ln of both sides


\ln(e^(kt)) = \ln((1+r)^t)

Rewrite as:


kt\ln(e) = t\ln(1+r)

Divide both sides by t


k = \ln(1+r)

Hence:


k(r) = \ln(1+r)

Solving (b): r(T2)

Equate
y(t) = y_02^(t/T_2) and
y(t) = y_0(1+r)^t


y_0(1+r)^t = y_02^(t/T_2)

Cancel out common terms


(1+r)^t = 2^(t/T_2)

Take t th root of both sides


(1+r)^(t*1/t) = 2^(t/T_2*1/t)


1+r = 2^(1/T_2)

Make r the subject


r = 2^(1/T_2)-1

Hence:


r(T_2) = 2^(1/T_2)-1

Solving (c): T2(k)

Equate
y(t) = y_02^(t/T_2) and
y(t) = y_0e^(kt)


y_02^(t/T_2) = y_0e^(kt)

Cancel out common terms


2^(t/T_2) = e^(kt)

Take ln of both sides


\ln(2^(t/T_2)) = \ln(e^(kt))

Rewrite as:


(t)/(T_2) * \ln(2) = kt\ln(e)


(t)/(T_2) * \ln(2) = kt*1


(t)/(T_2) * \ln(2) = kt

Divide both sides by t


(1)/(T_2) * \ln(2) = k

Cross multiply


kT_2 = \ln(2)

Make T2 the subject


T_2 = (\ln(2))/(k)

Hence:


T_2(k) = (\ln(2))/(k)

User Good Lux
by
5.3k points